A Break from Overtourism: Domestic Tourists Reclaiming Nature during the COVID-19 Pandemic - Margrét Wendt; Anna Dóra Sæþórsdóttir; Edda R. H. Waage (Tourism and Hospitality, 2022)
Natural areas are often of particular importance for residents as venues for recreation and domestic tourism. However, prior to the COVID-19 pandemic, overtourism was a major challenge for many nature-based tourism destinations worldwide, and led to a perceived restriction of tourism opportunities for residents. Iceland, one of the countries most associated with the concept of overtourism, witnessed a rapid reduction in international tourist arrivals after the emergence of the COVID-19 pandemic. At the same time, domestic tourism was unrestricted and, in fact, actively encouraged. Iceland in the summer of 2020 thus presents an interesting case for studying the experience of domestic tourists at previously overcrowded nature destinations. The study took place in Landmannalaugar, a nature destination known for crowding prior to the pandemic, and is based on 33 semi-structured interviews. Its results reveal that Icelandic residents perceived the break from overtourism as a benefit of the pandemic, and considered it a unique opportunity to reclaim nature destinations from which they had been displaced due to overcrowding by international tourists. Furthermore, they welcomed the chance to engage with fellow domestic tourists. The findings stress the importance of addressing the needs and wants of residents and supporting the development of domestic tourism.